LEVELS OF SELF-ACTUALİZATİON WİTH MANİFESTATİONS OF VİOLENCE İN STUDENTS STUDY OF THE RELATİONSHİP BETWEEN - Aygun, Karimli (Health and Society, 2024)
It is devoted to the study of the relationship between the manifestations of violence and the levels of self-actualization in students. In the study, the methodology of studying the effects of violence and Shostrom’s SAT methodology and the questionnaire prepared by the author were used. The study included 140 undergraduate students. It was determined that there is a negative correlation between the level of self-actualization of demands and the violence suffered. It became clear that the relationship between the primitive level of self-actualization and the verbal and non-verbal types of violence is bidirectional. At the same time, the relationship between different types of enjoyment and self-actualization is two-way. It can be concluded that as the levels of self-actualization increase, the likelihood of being bullied decreases. It was found that the relationship between the adequate level of self-actualization and the types of violence is positive. The research showed that the phenomenon of verbal and non-verbal violence in childhood causes quite a variety of psychological effects, such as trauma, trust problems, loss of personal self-confidence, self-loathing and the formation of a fearful/anxious personality, and it is very important to eliminate them. It can be concluded that students in order to eliminate the manifestations of violence, it is necessary to increase the personality qualities, including the opportunities for self-realization, and to create a favorable educational environment for this.